A Liquid Ventilator Prototype for Total Liquid Ventilation Preclinical Studies - Micheau, Philippe; Robert, Raymond; Beaudry, Benoit; Beaulieu, Alexandre; Nadeau, Mathieu; Avoine, Olivier; Rochon, Marie-Eve; Praud, Jean-Paul; Walti, Hervé (IntechOpen, 2011)
None